PENGGUNAAN MEDIA VIDEO TUTORIAL DALAM MENINGKATKAN KETERAMPILAN BERWUDU SISWA DI KELAS II SDN 25 AIR TAWAR SELATAN KOTA PADANG - Nurhidayah, Nurhidayah; Alfurqan, Alfurqan; Hidayat, Ajat (FASHLUNA, 2023)
This article examines the use of video tutorial media in improving students' tangible skills in grade II SDN 25 Air Tawar Selatan. Wudu is one of the legal requirements for prayer, if the student is not able to form properly, it will have an impact on the poor quality of the student's worship until he grows up. For this reason, it is necessary to know how teachers improve students' tangible skills in wudu practice materials by using video tutorial media. This research method is descriptive qualitative, while the data collection method used is observation, interview, and documentation. The result of this study is the process of using video tutorial media in grade II SDN 25 Air Tawar Selatan consisting of 3 stages, namely preparation, implementation, and final / evaluation stages. The supporting and inhibiting factors come from students, teachers, schools and the community environment. While the improvement of students' tangible skills is very good, the mistakes made by students in tangible are much reduced after using video tutorial media.